The Effect of Job Stress on Subjective Well-Being with Coping Style as Intervening - Raditya Wahyu Aji Pambudi; Adi Rahmat; Helwen Heri (Yayasan Education Al Aqsho Modern, 2022)
The purpose of this study was to determine whether work stress affects the Subjective Well-Being of police personnel mediated by coping style. The SEM-PLS method is a way to analyze latent variables and indicators/dimensions as well as carry out direct measurements. PLS analysis is a combination of path analysis, regression, and confirmatory factors. The research sites are several police institutions in the territory of Indonesia. The findings of this study can also provide input to the organization's management in designing strategies to reduce stress levels and increase individual subjective well-being in the workplace. The results of the study are also expected to be a stimulus to give more attention to future studies from academics and practitioners in investigating factors that can increase individual positive experiences such as subjective well-being.